Expansion of no-tillage practice in conservation agriculture in Brazil - Fuentes-Llanillo, Rafael; Telles, Tiago Santos; Soares Junior, Dimas; de Melo, Thadeu Rodrigues; Friedrich, Theodor; Kassam, Amir (Soil & tillage research, 2021)
•From 2006 to 2017, No-Till (NT) area increased by 84.9 % from 17.9 to 33.0 million ha.•NT area as a share of Total Area of crops changed from 51.2 to 61.0%.•The spread of NT system permitted the expansion of soybean crop to new tropical areas.•NT as a lone practice is no guarantee for production sustainability.•Quality efforts are required for adoption of three principles of Conservation Agriculture. Brazil is one of the countries in which the practice of No-Tillage (NT) has been most widely implemented as one of the three fundamental ecological principles of Conservation Agriculture (CA), crucial for the sustainability of the national agriculture. The first official data on the use of this practice were collected in the Agricultural Census of 2006 and after that again in 2017. For the first time in the country’s history these surveys provided primary data that made possible an analysis of the dynamics of the adoption of NT practice within the development of CA systems. Data supplied by special tabulation showed that the expansion of the NT practice throughout the country was strongly associated with the expansion of soybean-based cropping systems involving crops such as maize, wheat or cotton. In other words, NT practice improved soil moisture conditions and generated additional growing period that permitted the incorporation of soybean crop into CA cropping systems where it was not possible before. The increase in the NT area was substantial in Mato Grosso state, but was also evident in the region called MATOPIBA (comprising the states of Maranhão, Tocantins, Piauí and Bahia), i.e., the current agricultural frontier of the country, as well as in Rio Grande do Sul. In the regions where NT had already become the most common soil management system, e.g., in the South, this development occurred together with the area expansion of soybean-based cropping systems, showing that soybean is the most important crop in Brazil, in economic terms. However, the use of NT as a lone practice is no guarantee for sustainability, and technology transfer and adoption efforts are also required to reinforce the application by farmers of the other two ecological principles of CA which are permanent soil mulch cover and crop diversification through rotations and/or associations.